(untitled) (Sunari Penjor : Journal of Anthropology, 2025)
This study aims to understand how individual spread their religious identity through Instagram social media. The main focus of this study is how students express their religious identity more broadly. This study uses Social Identity Theory using the Hybrid Ethnography method to understand the social meaning of uploaded content, comments given, and interaction patterns that appear on digital platforms. The results of the study show that embedding verses of the holy book in Instagram bios not only reflects a strong religious identity, but also functions as a means to convey religious messages, seek personal motivation, and even as a form of digital preaching. In addition, students also express their religious identity through various other means, such as uploading religious content, and sharing spiritual songs. This study highlights the important role of Instagram in the religious life of students, the Instagram platform is not only a means to express religious identity, but also to share beliefs, and inspire others.